Maternal dexamethasone exposure alters synaptic inputs to gonadotropin-releasing hormone neurons in the early postnatal rat - Lim, Wei Ling *; Marshita Mohd Idris,; Felix Suresh Kevin,; Saga, Tomoko; Parhar, Ishwar S. (Frontiers Media, 2016)
Maternal dexamethasone [(DEX); a glucocorticoid receptor agonist] exposure delays pubertal onset and alters reproductive behavior in the adult offspring. However, little is known whether maternal DEX exposure affects the offspring’s reproductive function by disrupting the gonadotropin-releasing hormone (GnRH) neuronal function in the brain. Therefore, this study determined the exposure of maternal DEX on the GnRH neuronal spine development and synaptic cluster inputs to GnRH neurons using transgenic rats expressing enhanced green fluorescent protein (EGFP) under the control of GnRH promoter. Pregnant females were administered with DEX (0.1 mg/kg) or vehicle (VEH, water) daily during gestation day 13–20. Confocal imaging was used to examine the spine density of EGFP–GnRH neurons by three-dimensional rendering and synaptic cluster inputs to EGFP–GnRH neurons by synapsin I immunohistochemistry on postnatal day 0(P0) males. The spine morphology and number on GnRH neurons did not change between the P0 males following maternal DEX and VEH treatment. The number of synaptic clusters within the organum vasculosum of the lamina terminalis (OVLT) was decreased by maternal DEX exposure in P0 males. Furthermore, the number and levels of synaptic cluster inputs in close apposition with GnRH neurons was decreased following maternal DEX exposure in the OVLT region of P0 males. In addition, the postsynaptic marker molecule, postsynaptic density 95, was observed in GnRH neurons following both DEX and VEH treatment. These results suggest that maternal DEX exposure alters neural afferent inputs to GnRH neurons during early postnatal stage, which could lead to reproductive dysfunction during adulthood.